Association between dexamethasone treatment and the host response in COVID-19 patients admitted to the general ward - Justin de Brabander; Erik H. A. Michels; Christine C. A. van Linge; Osoul Chouchane; Renée A. Douma; Tom D. Y. Reijnders; Alex R. Schuurman; Tjitske S. R. van Engelen; Amsterdam UMC COVID-19 biobank study group; W. Joost Wiersinga; Tom van der Poll (Respiratory Research, 2022)
Abstract Dexamethasone improves clinical outcomes in COVID-19 patients requiring supplementary oxygen. We investigated possible mechanisms of action by comparing sixteen plasma host response biomarkers in general ward patients before and after implementation of dexamethasone as standard of care. 48 patients without and 126 patients with dexamethasone treatment were sampled within 48 h of admission. Endothelial cell and coagulation activation biomarkers were comparable. Dexamethasone treatment was associated with lower plasma interleukin (IL)-6 and IL-1 receptor antagonist levels, whilst other inflammation parameters were not affected. These data argue against modification of vascular-procoagulant responses as an early mechanism of action of dexamethasone in COVID-19.